MCDM Application on Indonesia Halal Food Development Strategy - Algaisya, Annisa Yasrien; Rosadhillah, Valencia Kirana (Islamic Economics Methodology, 2024)
This study tries to find strategies for the development of the halal food industry in Indonesia with one of the MCDM approaches, namely ANP. Based on the experts' answers, the results show that the biggest weight in the development of halal food in Indonesia is the strategy of strengthening the halal value chain ecosystem (0.33). Next are aspects of strengthening the local market (0.25) and aspects of institutional effectiveness (0.19). Last but not least is the product diversification strategy (0.16). Based on the results of this study, regulators can develop policies that support the establishment of halal centers as part of strengthening the value chain ecosystem. This can be done by providing fiscal incentives, technical assistance, and licensing that facilitate the establishment of halal centers. Then, regulators are expected to further encourage the standardization of domestic halal products by developing policies that facilitate the standardization process, including standard development, certification, and supervision of halal products.